Letter (copy) : Basque Children - Tewson, Vincent
1941-01-10 038-0036-001 International. HVT/AC/DT/469. 10th January, 1941. Mr. W. Elger, Scottish Trades Union Congress, 33, Elmbank Crescent, GLASGOW, C.2. Dear Mr. Elger, BASQUE CHILDREN. I received from the Dundee and District Union of Jute and Flax Workers on the 1st January last a letter in identical terms to that with which you quote as having received from the same Union. I think the best thing I can do is to send you a copy of my reply from which you will note the point we make about contributions coming through the International Solidarity Fund. Yours sincerely, Assistant Secretary. Letter. 292/946/38/36(I)